The Word (HATA) In the Qur’an Fundamental Statistical Study Preparation - Salam Khalil Alwan AL-Shujairi (Islamic Sciences Journal, 2026)
Arabic letters, including those of the Holy Quran, are divided into two types: structural letters and semantic letters. Semantic letters have multiple uses, including literal and metaphorical. One of the semantic letters mentioned in the Holy Quran is the preposition "Hata" (حتى), which appears 142 times in 138 verses. This letter has various uses, such as indicating direction or purpose. It precedes the verbal noun with different frequencies, and sometimes indicates the beginning of a condition or purpose. Scholars derived their principles from Arabic language, including the study of semantic letters like "Hata". They developed various rules regarding the implications of this letter, particularly in legal issues such as the rulings on demolition and marital relations before ritual purification. Due to differences among scholars regarding its implications, there are variations in legal opinions on many jurisprudential issues